Respuesta :
The distance between the horizontal legs be the distance between the 'x' values '-5' and '2'. 2+5=7 (It is +5 because the distance between -5 and 0 is 5*)
The distance between the horizontals is 7
Same with the vertical points, as the distance is 2. (1+1=2)
Considering that the pythagorean theorem is the a^2+b^2=c^2, and 'a' and 'b' are the sides, then you plug in '7' and '2', making the equation 7^2+2^2=c^2
49+4=c^2
53=c^2
c=sqrt(53)
Hope this helps.
The distance between the horizontals is 7
Same with the vertical points, as the distance is 2. (1+1=2)
Considering that the pythagorean theorem is the a^2+b^2=c^2, and 'a' and 'b' are the sides, then you plug in '7' and '2', making the equation 7^2+2^2=c^2
49+4=c^2
53=c^2
c=sqrt(53)
Hope this helps.
The distance between the two points can be found by Pythagoras
theorem, given that their horizontal and vertical distance apart are known.
- The distance of the horizontal leg is 7
- The distance of the vertical leg is -2
- The distance between the two points, c = [tex]\sqrt{53}[/tex]
Reasons:
The given points are; (-5, 1), and (2, -1)
The points expresses the following ordered pair;
(x₁, y₁) = (-5, 1)
(x₂, y₂) = (2, -1)
- The distance of the horizontal leg is; a = |x₂ - x₁| = 2 - (-5) = 7
- The distance of the vertical leg is; b = |y₂ - y₁| = -1 - 1 = -2
With Pythagoras theorem the direct distance between the points c can be
found using the formula [tex]c = \sqrt{a^2 + b^2}[/tex]
Where;
a = (x₂ - x₁)
b = (y₂ - y₁)
Therefore;
The distance between the two points by Pythagorean theorem is given as follows;
[tex]c = \sqrt{\left (x_{2}-x_{1} \right )^{2}+\left (y_{2}-y_{1} \right )^{2}}[/tex]
Which gives;
[tex]c = \sqrt{\left (-1-1 \right )^{2}+\left (2-(-5) \right )^{2}} =\sqrt{4 + 49} =\sqrt{53}[/tex]
- The distance between the two points, c = [tex]\sqrt{53}[/tex]
Learn more here:
https://brainly.com/question/13160273